Inovaţia socială în serviciile de sănătate - Tomescu, Cristina (Calitatea Vieții, 2009)
This article analyses the way social innovation is implicated in health services. Innovation was largely used in the postwar era in increasing the quality of medical services by innovating service management and adopting a new philosophy of sanitary policies. Welfare state itself has represented a social innovation, with profound implications upon citizen’s social rights to health services. Additionally, the concept of public health evolved to a larger approach which includes psychosocial elements and the concept of lifestyle.